The Effect of Audit Tenure, Audit Rotation, Audit Fee, Accounting Firm Size, and Auditor Specialization to Audit Quality - Shinta Permata Sari; Ayu Aris Diyanti; Rita Wijayanti (Universitas Muhammadiyah Surakarta, 2019)
The company management has a responsibility to run the company activities by reporting the resultsthrough financial statements. The role of an auditor is needed to mediate the management's interest and share holder’s concern.An auditor is an independent part of giving an opinion about the information contained in the financial statementsthroughits audit quality. Audit quality can be reduced if the auditor is not independent anymore. This study aims to analyze the effect of audit tenure, audit rotation,audit fee, accounting firm size, and auditor specialization to audit quality. The population of the study is manufacturing companies listed on the Indonesia Stock Exchange in2015-2017. The sample was taken by a purposive sampling method and obtained 50 companies as samples. Data were tested using logistic regression. The results of this study indicate that audit rotation,fee audit, and accounting firm size do not affect audit quality,meanwhile, the audit tenure and auditor specialization affect audit quality.